Desenvolvimento de método analítico para estudo de degradação forçada de cefalotina sódica na forma farmacêutica pó liofilizado para solução injetável - Rugani, Karen de Souza [UNESP] (2015)
Cephalothin (CET) is a semi-synthetic β-lactam antimicrobial compound, bactericidal, and it represents the prototype of cephalosporins, which belongs to the first-generation class. Cephalosporins present a larger spectrum of activity than penicillins and they are widely prescribed. Few analytical methods are described in the literature for the analysis of CET and to our knowledge rapid stability-indicating liquid chromatography (LC) methods for this compound have not been published elsewhere. A stability-indicating gradient reversed phase liquid chromatography (RP-LC) method has been developed for the quantitative determination of CET, in the presence of its impurities and degradation products generated from forced degradation studies, in samples of lyophilized powder for injection. The developed method is also applicable for the related substances determination in bulk drugs and pharmaceutical forms. The chromatographic separation was achieved on an Agilent Eclipse XDB-Phenyl, 250 mm x 4.6 mm, 5 μm column with mobile phase containing a gradient mixture of solutions A (aqueous ammonium phosphate buffer, pH 4.5) and B (acetonitrile) as mobile phase. The flow rate was 1.0 mL/min and the detection wavelength was 238 nm. The drug substance was subjected to stress conditions of hydrolysis, oxidation, photolysis, humidity and thermal degradation. Considerable degradation was found to occur in base, acid and oxidative stress conditions. In the developed high performance liquid chromatography (HPLC) method, the resolution between CET and its potential degradation products was found to be greater than 2.4, further, the peak purity of CET in all conditions were more than 99% proving the stability-indicating power of method. The less active metabolite of CET, desacetylcephalothin (impurity B), was identified and is showed significant formation especially in alkaline condition. This method is able to detect the degradation products of CET at a ...